A preliminary study: is fibulin 1 a friend or an enemy that needs to be silenced with siRNAs for mesothelioma? - Aksoy, Asude; Tektemur, Ahmet; Melek, Elif; Kayfeci, Mustafa; Uslu, Muhammed F.; Cosar, Ugurcan; Onalan, Ebru (Termedia Publishing House Ltd, 2020)
Introduction: The impaired balance between cell proliferation and cell death, followed the inability to receive the death signals, cells push towards the neoplasia pathway. Fibulin 1 (FBLN1) plays a role as a co-factor in the mechanism of action of a protease such as a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS-1), which has important roles in angiogenesis, can also act as both tumor suppressor gene (TSG) and an oncogene in the main constituent of the extra-cellular matrix. This preliminary study has investigated the effects of silencing FBLN1 with siRNA on autophagy, proliferation, apoptosis pathways in the MSM cell line. Material and methods: It was transfected siRNA specific to FBLN1 incubated MSM SPC212 cells, and compared with negative control siRNAs by a real-time polymerase chain reaction. It was determined apoptosis, proliferation, autophagy-related genes in mRNA levels. Results: It was observed that increased anti-apoptosis genes, such as CASP2, CASP7, DDFA, and BCL2, anti-apoptotic gene, reduced APAF1, CASP8. Proliferation induced through while increased ADAMTS1, CDH1, CDH6, CLON7, CSF3, MMP7, MMP13 genes. Autophagy increased via increasing MAP1LC3B, ATG-16L1 genes while decreased via suppressed ULK1, and ATG7 genes by silencing FBLN1 with siRNAs (p < 0.05). Conclusions: Proliferation can be induction with silencing of FBLN1 with siRNA in processing mechanism MSM. It was concluded that FBLN1 could be act as pleiotropic on autophagy, and apoptosis pathways in proliferation processing for MSM. Therefore we think that FBLN1 acts like a TSG. FBLN1 can be considered as a targeted treatment option in advanced stage MSM.
Keywords: mesothelioma; fibulin 1; autophagy; proliferation; apoptosis